Chemical content in Two Teak Woods (Tectona grandis Linn.F.) that has been used for 2 years and 60 years - Enih Rosamah; Fera Ferliyanti; Harlinda Kuspradini; Rudi Dungani; Pingkan Aditiawati (School of Life Sciences and Technology, Institut Teknologi Bandung, 2020)
Teak (Tectona grandis Linn F.) is classified as luxury wood and belongs to the durable wood, resistant to termite and fungal attacks. The purposes of this study were to analyze and compare the chemical content and bioactive compound of teak (T. grandis Linn F.) from Sumedang, West Java based on age of use. This study used teak woods of 2 and 60 years of use. The chemical components analyzed by determination of lignin, extractives, and ash content. Phytochemical compounds were analyzed by color changing of crude acetone extracts. The results showed that the teak wood with 2 years of use possessed lignin of 28.41%; cold water soluble extractives of 4.26%; hot water soluble extract of 5.12%; NaOH 1% soluble extractives of 19, 40; and alcohol:benzene (1:2) soluble extract of 6.21%; while ash content of 0.85%. Meanwhile teak wood after use of 60 years showed the lignin content of 29.82%; cold water extract of 1.56%; hot water extract of 2.56%; 1% NaOH soluble extract of 12.30%; alcohol:benzene (1:2) extract of 4.62%; ash content of 1.36%. The qualitative phytochemical test demonstrated both of teak wood after use of 2 years and use of 60 years contained flavonoids, tannins, triterpenoids, cumarins, and carbohydrates.